Corporate Turnarounds: The Duality of Retrenchment and Recovery - Schmitt, Achim; Raisch, Sebastian (Journal of Management Studies, 2013)
AbstractCorporate turnaround research has described retrenchment and recovery as contradictory forces that should be addressed separately. While a few scholars have argued that retrenchment and recovery are interrelated and may have to be integrated, others have contended that such arguments are flawed since they downplay the contradictions between the two activities. In this paper, we clarify the nature of the retrenchment–recovery interrelations, as well as their importance for turnaround performance. Drawing on the paradox literature, we argue that retrenchment and recovery form a duality: they are both contradictory and complementary. Integrating the two activities allows turnaround firms to create benefits that exceed the costs of their integration, which affects turnaround performance positively. We test our arguments through an empirical study of 107 Central European turnaround initiatives and find evidence for the assumed duality between retrenchment and recovery. Our main contribution is integrating the hitherto disparate theory perspectives of corporate turnaround into an overarching framework.